Measurement of the Top Quark Pair Production Cross Section in Proton-Proton Collisions at √[s]=13 TeV - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (Physical review letters, 2016)
The top quark pair production cross section is measured for the first time in proton-proton collisions at sqrt[s]=13 TeV by the CMS experiment at the CERN LHC, using data corresponding to an integrated luminosity of 43 pb^{-1}. The measurement is performed by analyzing events with at least one electron and one muon of opposite charge, and at least two jets. The measured cross section is 746±58(stat)±53(syst)±36(lumi) pb, in agreement with the expectation from the standard model.